GIVING WAQF BEHAVIOUR AMONG RIAU MUSLIM ENTREPRENEURS: THE ROLE OF RELIGIOSITY - Daharmi Astuti; Boy Syamsul Bakhri; Mufti Hasan Alfani; Mona Fairuz Ramli; Rasalhaque Daffa Taruna (International Conference On Law And Social Sciences, 2024)
Waqf plays a very important economic and social role in Islamic history, functioning as a source of financing for mosques, schools, research, hospitals, social services and defense, namely before Indonesia's independence, because in Indonesia there were once Islamic kingdoms, Waqf had to be managed productively so that it can contribute to improving the welfare of the community and assist the government in improving the welfare and standard of living of the community. From the results of a study by the Syarief Hidayatullah State Islamic University, Jakarta in 2006, it shows that recorded waqf assets in Indonesia nationally reached almost 363 thousand plots of land, with a nominal value estimated at IDR 590 trillion. This is equivalent to more than 67 billion US dollars if the exchange rate is IDR 9,250/dollar. This number is certainly very large. If all the waqf assets were sold, the proceeds could cover 100% of the total foreign debt of the Government of the Republic of Indonesia in 2008, which amounted to "only" 60 billion US dollars. This is just to make it easier to understand how large waqf assets are in Indonesia. The implementation of Waqf is currently not going well, due to the lack of maximum role of the Government which is assisted by several BWIs (Indonesian Waqf Board), as happened in Riau Province which was due to the implementation of Waqf not going well. So in this research that will be the object The research target is the population in Pekanbaru City. The main aim of this research is to measure the level of awareness and willingness of the Muslim community to carry out waqf. In addition, this research aims to determine the factors that contribute to the provision of waqf to Muslims in Malaysia and Indonesia. Furthermore, this study hopes to provide policy input and recommendations to relevant waqf authorities and other government agencies on how to improve the efficiency of waqf institutions. The constructs examined in this research are knowledge, religiosity, trust, awareness, perceived ihsan, perceived risk and Islamic egalitarianism.